The Effectiveness of Hyperbaric Oxygen Therapy for Management Osteoradionecrosis in Jaw: A Meta-Analysis - Leesomprasong, Thanyaporn; Thaweedej, Sasithorn (Journal of The Department of Medical Services, 2021)
Background : Osteoradionecrosis of the jaw is a severe complication of radiotherapy in patients with head and neck cancer. However, there is insufficient empirical results to support the effect of hyperbaric oxygenation treatment.Objective : The purpose of this meta-analysis study was to collect data and evidence on the effect of hyperbaric oxygenation in management of osteoradionecrosis.Method : Systematically and meta-analysis study search for related article from the Cochrane Database of Systematic Reviews (CDSR), PubMed, Google scholar and manual search at Institute’s library.Result : Five articles were extracted. Risk ratio was calculated and pooled data at 95% confidence interval and random effect model was used (RR=1.17 (95% CI=0.975-1.404, p=0.92)). The result is high heterogeneity of data (I2=69.8%). Asymmetric funnel plot was found (Begg’s test p-value=0.624, Egger’s test p-value = 0.422) which stated an absence of publication bias or small study effect.Conclusions : The use of hyperbaric oxygenation for management of osteoradionecrosis has more healing chance compared to the unused group, statistically insignificant, but the evidence is inconclusive from high heterogeneity of data (I2 = 69.8%). However, the limitations in study design are result in few high-quality studies. Further study is still required in the future for a high-quality trial.